Multisystem Inflammatory Syndrome and Autoimmune Diseases Following COVID-19: Molecular Mechanisms and Therapeutic Opportunities - Hosseini, Parastoo; Fallahi, Mohammad Sadegh; Erabi, Gisou; Pakdin, Majid; Zarezadeh, Seyed Mahdi; Faridzadeh, Arezoo; Entezari, Sarina; Ansari, Arina; Poudineh, Mohadeseh; Deravi, Niloofar (Frontiers in Molecular Biosciences, 2022)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2), has led to huge concern worldwide. Some SARS-CoV-2 infected patients may experience post–COVID-19 complications such as multisystem inflammatory syndrome, defined by symptoms including fever and elevated inflammatory markers (such as elevation of C reactive protein (CRP), erythrocyte sedimentation rate, fibrinogen, procalcitonin test, D-dimer, ferritin, lactate dehydrogenase or IL-6, presence of neutrophilia, lymphopenia, decreased albumin, and multiple organ dysfunction). Post–COVID-19 complications may also manifest as autoimmune diseases such as Guillain-Barré syndrome and systemic lupus erythematosus. Signaling disorders, increased inflammatory cytokines secretion, corticosteroid use to treat COVID-19 patients, or impaired immune responses are suggested causes of autoimmune diseases in these patients. In this review, we discuss the molecular and pathophysiological mechanisms and therapeutic opportunities for multisystem inflammatory syndrome and autoimmune diseases following SARS-CoV-2 infection with the aim to provide a clear view for health care providers and researchers.